2021
DOI: 10.1101/2021.09.27.21264163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody responses against SARS-CoV-2 variants induced by four different SARS-CoV-2 vaccines

Abstract: Emerging and future SARS-CoV-2 variants may jeopardize the effectiveness of vaccination campaigns. We performed a head-to-head comparison of the ability of sera from individuals vaccinated with either one of four vaccines (BNT162b2, mRNA-1273, AZD1222 or Ad26.COV2.S) to recognize and neutralize the four SARS-CoV-2 variants of concern (VOCs; Alpha, Beta, Gamma and Delta). Four weeks after completing the vaccination series, SARS-CoV-2 wild-type neutralizing antibody titers were highest in recipients of BNT162b2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
2
13
0
Order By: Relevance
“…Instead, again vaccine type or regimen (homologous vs heterologous) received had the largest effect upon ACE2 binding inhibition. The VoCs themselves followed a previously published pattern ( 9 , 22 , 67 ), with the lowest reduction for the Alpha variant, and the highest for the Beta and Gamma variants. It should be stated that in our analysis of longitudinal samples, there is a wide variety of timeframes post-vaccination, meaning that initial samples are collected both before, during and after the initial peak response at around 28 days.…”
Section: Discussionsupporting
confidence: 72%
“…Instead, again vaccine type or regimen (homologous vs heterologous) received had the largest effect upon ACE2 binding inhibition. The VoCs themselves followed a previously published pattern ( 9 , 22 , 67 ), with the lowest reduction for the Alpha variant, and the highest for the Beta and Gamma variants. It should be stated that in our analysis of longitudinal samples, there is a wide variety of timeframes post-vaccination, meaning that initial samples are collected both before, during and after the initial peak response at around 28 days.…”
Section: Discussionsupporting
confidence: 72%
“…For Pfizer, antibody levels reduced from a median of 7506 U/mL at 21-41 days to 3320 U/mL at 70 or more days. For the AstraZeneca vaccine, antibody levels reduced from a median of 1201 U/mL at 0-20 days to 190 U/mL at 70 or more days [35]. According to the information in the leaflet, the efficacy range of the AstraZeneca vaccine is close to the efficacy of Johnson & Johnson, but lower than Pfizer and Moderna.…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost is the reliance on neutralizing antibody titers as a predictor of protection against infection and transmission. Although the analyses here, and elsewhere suggest a strong relationship between neutralizing antibody titers and protection at the population level [4, 18] and individual level [33], other parts of the immune system, such as T-cells, also play key roles in protection, especially against severe disease. Second, our analyses use population averages for estimates of protection against infection and transmission and ignore age-specific variation among individuals (as well as other factors).…”
Section: Discussionmentioning
confidence: 76%
“…We found that a third dose could substantially reduce transmission, especially in highly vaccinated populations, and the effect was larger in populations with lower acquired immunity from infection and when contact rates (which scale R 0 ) were higher. We showed that neutralizing antibodies are strongly correlated not just with protection against symptomatic disease [4, 18], but also with protection against all infection and transmission given infection (Figures 1, S4). This allowed us to estimate the effect of waning and boosting on transmission, and the pathogen reproductive number R t .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation